Comparative evaluation of diode laser versus argon laser photocoagulation in patients with central serous retinopathy: A pilot, randomized controlled trial [ISRCTN84128484] - Venkatesh Pradeep; Sinha Rajesh; Verma Lalit; Tewari HK (BMC Ophthalmology, 2004)
Abstract Background To evaluate the efficacy of diode laser photocoagulation in patients with central serous retinopathy (CSR) and to compare it with the effects of argon green laser. Methods Thirty patients with type 1 unilateral CSR were enrolled and evaluated on parameters like best corrected visual acuity (BCVA), direct and indirect ophthalmoscopy, amsler grid for recording scotoma and metamorphopsia, contrast sensitivity using Cambridge low contrast gratings and fluorescein angiography to determine the site of leakage. Patients were randomly assigned into 2 groups according to the statistical random table using sequence generation. In Group 1 (n = 15), diode laser (810 nm) photocoagulation was performed at the site of leakage while in Group 2 (n = 15), eyes were treated with argon green laser (514 nm) using the same laser parameters. Patients were followed up at 4, 8 and 12 weeks after laser. Results The mean BCVA in group 1 improved from a pre-laser decimal value of 0.29 ± 0.14 to 0.84 ± 0.23 at 4 weeks and 1.06 ± 0.09 at 12 weeks following laser. In group 2, the same improved from 0.32 ± 0.16 to 0.67 ± 0.18 at 4 weeks and 0.98 ± 0.14 at 12 weeks following laser. The improvement in BCVA was significantly better in group 1 (p < 0.0001) at 4 weeks. At 4 weeks following laser, all the patients in group1 were free of scotoma while 6 patients in group 2 had residual scotoma (p < 0.05). The mean contrast sensitivity in group 1 improved from pre-laser value of 98.4 ± 24.77 to 231.33 ± 48.97 at 4 weeks and 306.00 ± 46.57 at 12 weeks following laser. In group 2, the same improved from 130.66 ± 31.95 to 190.66 ± 23.44 at 4 weeks and 215.33 ± 23.25 at 12 weeks. On comparative evaluation, a significantly better (p < 0.001) improvement was noted in group 1. Conclusion Diode laser may be a better alternative to argon green laser whenever laser treatment becomes indicated in patients with central serous retinopathy in terms of faster visual rehabilitation and better contrast sensitivity. In addition, diode laser also has the well-recognized ergonomic and economic advantages.